Something to talk about [videorecording (DVD)] - Hallström, Lasse; Roberts, Julia, 1967-; Duvall, Robert; Rowlands, Gena; Sedgwick, Kyra; Quaid, Dennis (Warner Home Video, 2010)
The story of Grace, a woman with a "picture-perfect life," whose reaction to the infidelities of her husband Eddie turns the lives and loves of the people around her into something like falling dominoes.